Arabica Coffee (Coffea Arabica) Fruit Skin Potential Towards the Increase of Fibroblast Cells Amount Within Socket Post Tooth Extraction of Male Wistar Mouse - Ahmad Masruri; Agus Sumono; Tecky Indriana (Health Notions, 2019)
Background: Tooth extraction can cause wound in hard tissue and soft tissue inside oral cavity. Wound healing process involves cell proliferation especially fibroblast cells. To accelerate fibroblast cell proliferation alternative substance that can accelerates wound healing process is needed which is arabica coffee fruit skin. Arabica coffee fruit skin contains substances such as polyphenols, tannin, chlorogenic acid, and caffeine expected to be able to stimulate fibroblast cells amount. Objective: To understand arabica coffee fruit skin potential towards increase in number of fibroblast cells on the socket after tooth extraction. Method: The design of this research was post test only control group with sample size of 24 wistar mouse. The samples used were divided into two groups which are control and treatment group. Then treatment was given in 3 days, 5 days, and 7 days. Then they were decapitated to undergo tissue processing with HE coloring and post tooth extraction socket fibroblast cells counting. Acquired data then analyzed used One Way ANOVA and LSD test. Result: Fibroblast cell amount increased significantly (p